Bibliometric Analysis of Social Entrepreneurship (2018-2023) - Zaenul Muttaqien; Imam Mukhlis (Formosa Journal of Science and Technology, 2023)
Social entrepreneurship is a topic of great interest to researchers as implementations in this field are increasing in number. This study aims to map an overview of research using the topic of social entrepreneurship. Bibliometric analysis is used to assess the performance of scientific articles based on the metadata that has been obtained. This research explores (1) the number of article publications by year (2) the journal where the author published the article (3) the affiliation of the researcher who published the article (4) the country where the researcher published the article (5) the field of study of the researcher who published the article. Data was collected from the Scopus database with the keyword Social entrepreneurship from 2018 to 2023, in the form of scientific articles and using English languange. The presentation is in the form of tables and graphs while the publication development mapping image is visualized using vosviewer.